PROBLEMS OF PLANTATION GROWING OF ST. JOHN’S WORT (HYPERICUM PERFORATUM L.) - Pospielov, Sergii; Pospielova, Ganna; Semenko, Maksym (Sworld-Us Conference proceedings, 2023)
St. John’s wort (Hypericum perforatum L.) is a medicinal plant widely used in the world for the production of medicines and dietary supplements. This encourages pharmaceutical companies and agricultural enterprises to introduce St. John’s wort into cultur